Reflections on the European Union’s participation in negotiations of the global plastic pollution instrument under international environmental law - Xu, Qi; Zhang, Mingyang; Han, Shuli (Frontiers in Marine Science, 2024)
Increasing plastic pollution is looming worldwide, damaging biodiversity, marine ecosystems, and human health. At the global level, no overarching normative framework sets out the specific rules and principles of general application in international environmental law, leading to difficulties in compliance and enforcement of plastic pollution governance. Developing an effective and legally binding instrument to tackle this emerging issue is imperative. The United Nations Environment Assembly (UNEA) has called for developing an international legally binding instrument on plastic pollution, including in the marine environment, based on plastic’s full lifecycle approach. As one of the active participants in the negotiations, the European Union (EU) has discussed various aspects of the instrument in detail and sought to introduce the EU governance experience at the international level. This article develops a framework that considers contextual, actor, and process factors to assess the extent of achieving EU targets. On this basis, we argue that the EU’s objectives for the international instrument may be achieved at a high level. However, how the EU responds to challenges will also impact subsequent development, which may require the EU to adopt a more moderate stance and compromise on some controversial issues.